On the species specificity of the interaction of LFA-1 with intercellular adhesion molecules. - Johnston, S; Dustin, M; Hibbs, M; Springer, T (1990)
Species restrictions in immune cell interactions have been demonstrated both in Ag-specific responses of T lymphocytes and the phenomenon of natural attachment. To determine the possible contribution of adhesion receptors to these restrictions, we have studied binding between the murine and human homologues of LFA-1 (CD11a/CD18) and ICAM employing purified human LFA-1 and ICAM-1 (CD54) bound to solid substrates. Murine cell lines bind to purified human LFA-1 through ICAM-1 and at least one other counter-receptor. This provides evidence for multiple counter-receptors for LFA-1 in the mouse as well as in the human. In contrast to binding of murine ICAM-1 to human LFA-1, murine LFA-1 does not bind to human ICAM-1. The species specificity maps to the LFA-1 alpha subunit, because mouse x human hybrid cells expressing the human alpha subunit associated with a mouse beta subunit bind to human ICAM-1, whereas those with a human beta subunit associated with a murine alpha subunit do not. Increased adhesiveness for ICAM-1 stimulated by phorbol esters could be demonstrated for hybrid LFA-1 molecules with human alpha and murine beta subunits.